Isolation of bacteria from diesel contaminated soil for diesel remediation (Journal of Bio-Science, 2019)
This study is aimed at isolating bacterial species that inhabit diesel contaminated soil and also screened these isolates for the ability to be used for remediating diesel contaminated environment using their potential to degrade diesel as carbon and energy source. Top soil sample was collected from an ancient diesel-powered generator house in Minna, Nigeria, in a sterilized plastic container while diesel oil was obtained from local petrol bunk. Four bacterial isolates were isolated from the diesel contaminated soil sample and were screened for their ability to degrade diesel using mineral salt medium (MSM). The isolates with highest biodegradation potential were identified as Bacillus subtilis and Bacillus cereus. The optimum pH (5, 6, 7 and 8) and hydrocarbon concentration (1%, 2%, 5% and 10%) of the isolate was determined by spectrophotometry and the result revealed that the optimum pH for biodegradation of diesel by Bacillus subtilis and Bacillus cereus, was 7 (1.170) and 8 (1.745) respectively while the optimum hydrocarbon concentration degradation for both isolates was 5% (2.22) and 1% (2.37) respectively. The results of this study showed that these isolates were able to degrade diesel and can be useful for large scale bioremediation of diesel contaminated soils.J. bio-sci. 28: 33-41, 2020